Treatment of Cutaneous Melanoma of the Head and Neck With Wide Local Excision Versus Mohs. (12th April 2021) - Namin, Arya W.; Oudin, Edouard M.; Tassone, Patrick T.; Galloway, Tabitha L.I.; Dooley, Laura M.; Zitsch, Robert P.
Abstract : Objectives: Determine if Mohs micrographic surgery (MMS) is associated with improved overall survival compared to wide local excision (WLE) when treating cutaneous melanoma of the head and neck (CMHN) and to report the proportion of patients treated with MMS versus WLE who also underwent sentinel lymph node biopsy (SLNB). Methods: Retrospective cohort study of the National Cancer Database (NCDB) analyzing the overall survival of patients diagnosed with T1 to T4 CMHN between 2004 and 2016 who were treated with either WLE or MMS. Results: On multivariable analysis, treatment with WLE versus MMS was not significantly associated with overall survival (HR, 1.094; 95% CI, 0.997–1.201). On multivariable analysis, lower Charlson‐Deyo score (HR, 0.489; 95% CI, 0.427–0.560), negative margins (HR, 0.754; 95% CI, 0.705–0.807), and N0 classification (HR 0.698; 95% CI, 0.668–0.730) were associated with improved overall survival. Seventy‐seven percent of patients treated with MMS did not undergo SLNB, while 45% of patients treated with WLE did not undergo SLNB ( P < .001). Conclusions: No difference in overall survival between MMS and WLE when treating CMHN. Patients treated with MMS were significantly less likely to undergo SLNB, suggesting an opportunity for enhancement of multidisciplinary care. Level of Evidence: 4 Laryngoscope, 131:2490–2496, 2021